The structure of the social capital of female entrepreneurs: A pilot study on selected regions of the Republic of Serbia and the Republic of Austria - Stosic Panic, Danijela; Kircher, Monika (Industrija, 2017)
The paper presents the results of a pilot study of the entrepreneurial activity of women in selected regions of the Republic of Serbia and the Republic of Austria, focusing on the components of the social capital of female entrepreneurs. Bearing in mind the importance of social capital for starting the entrepreneurial activity, and for the business performance of entrepreneurs, the study was conducted in order to identify the basic characteristics and possible differences in business discussion networks as forms of social capital of Serbian and Austrian female entrepreneurs. A field research was conducted on a sample of female entrepreneurs from urban areas in the Republic of Serbia and the Republic of Austria. The obtained results confirm the expectations that family members and friends are essential sources of information and business advice for female entrepreneurs, and that there are relatively more women in the business discussion networks of Serbian and Austrian female entrepreneurs. The structures of the business discussion networks of female entrepreneurs from the selected regions of Serbia and Austria show similarities in the majority of the analyzed aspects. These results will enrich the body of knowledge about the entrepreneurial activity of women in the analyzed countries and they may represent a starting guideline for defining support programs for the entrepreneurial engagement of women.